1989
DOI: 10.1128/jb.171.6.3391-3405.1989
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional control of puc operon expression of B800-850 light-harvesting complex formation in Rhodobacter sphaeroides

Abstract: The puc operon of Rhodobacter sphaeroides comprises the pucBA structural genes which encode B800-850 light-harvesting ,I and a polypeptides, respectively. Northern (RNA) blot hybridization analysis of puc operon expression has identified two pucBA-specific transcripts. The small (0.5-kilobase [kb]) transcript encodes the 0i and a polypeptides and, under photoheterotrophic growth conditions, was approximately 200-fold more abundant than the large (2.3-kb) transcript. The 5' end of the 0.5-kb transcript was mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 40 publications
5
91
1
Order By: Relevance
“…Similarly, hemN was expressed aerobically at a low level with hemZ being off, but both showed increased expression when cells were shifted to anaerobic conditions as a result of the fact that both are under FnrL control (19,56). The expression level of pucC relative to pucBA is ϳ4 -8%, which is entirely consistent with the Northern hybridization results (33) and lacZ fusion studies (53) reported earlier, despite the fact that all of these genes reside in the pucBAC operon. Further, the expression of puhA (60) as well as pufBA (32) shows low expression under aerobic conditions as observed here, but both loci show increased expression as light intensity decreases.…”
Section: Effect Of Oxygen and Light On R Sphaeroides Transcriptomesupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, hemN was expressed aerobically at a low level with hemZ being off, but both showed increased expression when cells were shifted to anaerobic conditions as a result of the fact that both are under FnrL control (19,56). The expression level of pucC relative to pucBA is ϳ4 -8%, which is entirely consistent with the Northern hybridization results (33) and lacZ fusion studies (53) reported earlier, despite the fact that all of these genes reside in the pucBAC operon. Further, the expression of puhA (60) as well as pufBA (32) shows low expression under aerobic conditions as observed here, but both loci show increased expression as light intensity decreases.…”
Section: Effect Of Oxygen and Light On R Sphaeroides Transcriptomesupporting
confidence: 80%
“…However, these studies have been by necessity selective, and for the most part the overwhelming majority of these genetic elements comprising the photosynthetic lifestyle have never been investigated under the diverse environmental conditions described here. Photosynthesis Gene Cluster-As previously described for those genes encoding the apoproteins of the spectral complexes (19,32,33), there is a wealth of expression data, but for the most part the majority of the genes of the PS gene cluster of R. sphaeroides 2.4.1 have never been studied, except to note that their expression is higher under photosynthetic growth conditions relative to aerobic growth. In Fig.…”
Section: Effect Of Oxygen and Light On R Sphaeroides Transcriptomementioning
confidence: 99%
See 1 more Smart Citation
“…Radioactive probes were made by using highly purified plasmid DNA containing puf (pUI655), puc (pUI624) (29), cycA (pUI661), and puhA (pUI660) (26a) ( Table 1). All procedures have been described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…This study focuses on the mechanism of transcriptional control of the PS genes, in particular the ptlc operon, which encodes the structural polypeptides (Kiley & Kaplan, 1987) and assembly factor(s) (Gibson e t al., 1992;Lee et al, 1989b) for the LH I1 complex. Expression of most of the PS genes, includingptlc, depends on oxygen tension.…”
Section: Introductionmentioning
confidence: 99%